2009
DOI: 10.1002/jid.1598
|View full text |Cite
|
Sign up to set email alerts
|

Understanding poverty dynamics in Kenya

Abstract: Combining qualitative-quantitative approaches, we examined the reasons behind household movements into and out of poverty across Kenya, and how they differ by livelihood zones. Among the 4,773 households studied, 42% were poor 15 years ago and 50% are poor at the present time. Over the same period, 12% of the households escaped poverty, while another 20% fell into poverty. While some national trends were evident-such as the role of health problems in driving people into poverty and the importance of off-farm i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
46
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 32 publications
7
46
1
Order By: Relevance
“…Similarly, at the micro-level there is evidence that crop production is a pathway from poverty. In Kenya, for example, a national survey revealed that of the sampled households that moved out of poverty between 1990 and 2005, half attributed their success to investment in agriculture (Kristjanson et al 2010). Similarly, 70 % of households that moved out of poverty in Uganda between 1980 and 2004 stated that the main driver of ascent was agriculture (Krishna et al 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, at the micro-level there is evidence that crop production is a pathway from poverty. In Kenya, for example, a national survey revealed that of the sampled households that moved out of poverty between 1990 and 2005, half attributed their success to investment in agriculture (Kristjanson et al 2010). Similarly, 70 % of households that moved out of poverty in Uganda between 1980 and 2004 stated that the main driver of ascent was agriculture (Krishna et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Of the reasons given for graduation from poverty in Kenya, only 23 % of households cited increased land under cultivation, compared to 49 % who cited crop diversification or commercialization. In the zone with low potential for crop production, one-half of the households moving out of poverty attributed this to crop diversification away from maize to higher-value crops (Kristjanson et al 2010). Not all forms of commercialization are necessarily pathways from poverty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means prioritizing investments in programs targeted at poor or vulnerable households, such as transfers of cash, vouchers, food, or other goods, as suggested by poverty dynamics research in the region (Barrett et al 2006;Kristjanson et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…fertility and crop yields, poor market access, constrained access to land, and high inflation (Nelson et al 2010;Yamano et al 2011;Jayne et al 2006). Both poverty levels and household food insecurity are rising across East Africa (Charles et al 2010;Kristjanson et al 2010; Thornton et al 2011).…”
Section: Introductionmentioning
confidence: 99%